计算(2ab^2)^-2·(a^2·b)^2/(3a^3·b)^2·(ab^3)^-2
2个回答
原式=(a^4b²*a²b^6)/(4a²b^4*9a^6b²)
=a^6b^8/36a^8b^6
=b²/36a²
相关问题
计算 (a^2b-ab-a+1)/(ab^2+3ab-b-3)÷(a^2+a_2)/(b^2+b-6)
a^3+a^2b+ab^2-a^2b-ab^2-b^2 计算,
有一道题目是:“计算(2a^3-3a^2b-2ab^2)-(a^3-2ab^2+b^3)=(3a^2b-a^3-b^3)
计算:b/a-b加上b^3/a^3-2a^2b+ab^2除以ab+b^2/b^2-a^2
计算a+9b/3ab-a+3b/3ab=( ) a^2b^3/(2a^-1b^2)^-3=( )
3(3a^2+2ab-b^2)*(-ab)-3a^2(ab-b^2)
计算:(-a)^2(2-3ab)+3a^2(ab+1/3b-1)
计算分式:b^4/(a-b)^2 乘 a^3+ab^2-2a^2b/b^3 除以b^2-a^2/ab+b^2
计算:(1)a^-2b^-3·(-3a^-1b^2)÷6a^-4b^-2 (2)(3ab)^-3(2ab^-1)^-2
计算:2ab[(2ab)²-3b(ab+a²b)-ab²]